Sistema de iluminação de fotobiorreator baseado em POF para cultivo de microalgas - Manchego, Alfredo Omar Córdova (2018)
Increased demand in the consumption of fossil fuels in industrial production, in addition has led to an increase in air pollution on the planet. As an alternative to this problem, this paper proposes the study and development of a natural lighting system based on solar tracker, Fresnels lens and plastic optical fibers (POFs), as a viable technology for cultivation of microalgae for the generation of biomass to biofuel production, supplements and other feedstocks. The lighting system proposed consists of the optimization of a photobioreator (PBR) for small scale microalgae cultivation, low cost, and easy maintenance, compared to the existing systems. The PBR illumination through a fiber bundle, where at one of its ends we have the convergence of the sun's rays, by a Fresnel lens implemented in a solar tracking system. Initially, the current paper is divided in three stages. The first session describes the study of microalgae, type of PBRs and conditioning of POFs in the internal lighting of a PBR, aiming a high concentration of light and energy optimizing the lighting process with holes and grooves in the POF. The second session, presents the study of the improvements possibilities that aim to homogenize the lighting to be distributed inside the PBR. Finally, comparative results of the experiments of the microalgae cultivation are described, carried out in parallel cultivation, with the objective of surpassing the biomass production. As a result there was 18.4% increase in the production of more biomass in the PBR-Flat plate.